2021
DOI: 10.1021/acs.jpcb.1c04609
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Solution-Blended Graphene Nanoplatelets/Polyether-Ether-Ketone Nanocomposites

Abstract: A lightweight composite with outstanding damping effects and impact resistance is significant for the design of functional structures in advanced equipment, such as aircraft and space vehicles. In this paper, the mechanical properties of solutionblended graphene nanoplatelets (GNPs)/polyether-ether-ketone (PEEK) nanocomposites were characterized by both experimental and numerical methods. It can be found that the layer number and packing configuration of graphene layers are critical to the efficiency of energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…For the use of GO as structural materials, many efforts have been made to develop GO-based composites with ideal mechanical properties in the last decade [19][20][21]. The authors have investigated the physical mechanisms of energy absorption, while graphene and GO are used to reinforce engineering plastics [22]. However, the use of GO in shockabsorbing materials is still limited due to the low fracture toughness as a result of the addition of GO.…”
Section: Introductionmentioning
confidence: 99%
“…For the use of GO as structural materials, many efforts have been made to develop GO-based composites with ideal mechanical properties in the last decade [19][20][21]. The authors have investigated the physical mechanisms of energy absorption, while graphene and GO are used to reinforce engineering plastics [22]. However, the use of GO in shockabsorbing materials is still limited due to the low fracture toughness as a result of the addition of GO.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of nano‐fillers toughening polymers, like microcrack, interfacial sliding, pull‐out, [ 43 ] may not be the direct reason to mitigate shock waves. According to the literature, [ 44 ] shock energy dissipation ability of nano‐fillers modified composites depends on impedance mismatch between fillers and polymer matrix and can be improved by mediating the dispersity and alignment, partial shock wave is reflected in their interface to dissipate more energy. Combining the testing results above, the reason that the shock wave attenuation ability may depend on the structure and dispersion status of nano‐carbon fillers.…”
Section: Resultsmentioning
confidence: 99%
“…This dimension provides an optimal balance between computational efficiency and accuracy, according to the literature. [19] Sine-alternating shearing model [35,36] is used in this study to forecast the dynamic modulus of nanocomposites, as shown in Figure 4a. The nonequilibrium simulation of shearing covers five sinusoidal alternating strain periods with 20% peak shear strain and was divided into 100 phases to prevent incorrect molecule configurations.…”
Section: Molecular Models For Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…[15,16] The impact response of coarse crystal models of polyetheretherketone, polyethylene, and polyurea was carried out by molecular modeling techniques. [17][18][19] For example, the improvement of graphene on the mechanical properties of the substrate has been studied based on stacked graphene configurations, and the effect of graphene on the impact energy dissipation was also explored. [20][21][22] These findings indicate that more graphene layers and the angle of layers perpendicular to the impact direction have higher energy dissipation capacities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation